2014
DOI: 10.1002/jwmg.745
|View full text |Cite
|
Sign up to set email alerts
|

Home range and resource selection by GPS-monitored adult golden eagles in the Columbia Plateau Ecoregion: Implications for wind power development

Abstract: Recent national interest in golden eagle (Aquila chrysaetos) conservation and wind energy development prompted us to investigate golden eagle home range and resource use in the Columbia Plateau Ecoregion (CPE) in Washington and Oregon. From 2004 to 2013, we deployed satellite transmitters on adult eagles (n = 17) and monitored their movements for up to 7 years. We used the Brownian bridge movement model (BBMM) to estimate range characteristics from global position system (GPS) fixes and flight paths of 10 eagl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 37 publications
(55 reference statements)
9
81
0
Order By: Relevance
“…There has been an increasing interest in the study of bird movements in relation to wind-power generation on both raptor (Duerr et al 2012;Katzner et al 2012;Watson et al 2014) and non-raptor species (Corman and Garthe 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing interest in the study of bird movements in relation to wind-power generation on both raptor (Duerr et al 2012;Katzner et al 2012;Watson et al 2014) and non-raptor species (Corman and Garthe 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Often this process requires a two-phase approach, with an initial survey to estimate resource selection functions that can be used in phase two to assign survey plot locations (Manly et al, 2002b) The variation we observed in error due to sampling speaks to the need to adjust sampling to account for local eagle ecology. For example, golden eagles can show many types of seasonal movements (Watson, 2010;Watson et al, 2014;Braham et al, 2015). Although an eagle in California desert may spend all year tightly on a territory, eagles counted there may include seasonal migrants to the region and local eagles may show altitudinal or short-distance seasonal movements that influence detection rates.…”
Section: Improving Point Count Samplingmentioning
confidence: 99%
“…Raptors can also concentrate on the wintering grounds, when territorial boundaries are relaxed (Olson 2006, Elliott et al 2011, Watson et al 2014. The Christmas Bird Count (CBC) is a long-term, continent-wide, citizen sciencebased winter bird survey (National Audubon Society 2014) with geographic coverage that considerably overlaps with several raptor species' winter ranges.…”
Section: Introductionmentioning
confidence: 99%